Macular morphologic changes following successful retinal detachment repair by scleral buckling surgery - Petrović, Nenad; Todorović, Dušan; Srećković, Sunčica; Šarenac Vulović, Tatjana; Jovanović, Mihailo; Randjelović, Danijela (Vojnosanitetski pregled, 2023)
Background/Aim. Spectral domain optical coherence tomography (SDOCT) is very useful for the accurate examination of macular microstructure. The aim of this study was to evaluate macular morphologic changes after successful retinal detachment (RD) surgery by scleral buckling (SB) using SDOCT and assess their impact on vision repair. Methods. SDOCT examination was performed in 1, 6, and 12 months in 27 eyes following SB surgery with the successful anatomical repair of rhegmatogenous RD, which also affected the macular region. The examination was performed in a 6 mm diameter central macular region and included measurements of the central foveal thickness, average total retinal thickness (TRT), and thickness of the inner and outer retinal layer (ORT) separately. The numerical values of parameters for each operated eye were compared with those of the fellow (control) eye of each patient. The condition of the external limiting membrane (ELM) and inner segment (IS) and outer segment (OS) of the photoreceptors was also examined. Results. The mean TRT and ORT in the reattached regions in the operated eyes were significantly thinner than the corresponding regions of the fellow (control) eye, and throughout the follow-up period, the difference was statistically significant. There was a statistically significant difference in TRT (after 1 month, p = 0.021, after 6 months, p = 0.026, after 12 months, p = 0.027) and ORT (after 1 month, p = 0.018, after 6 months, p = 0.019, after 12 months, p = 0.021) between the eyes with a longer preoperative duration of macular detachment (MD) of 2 weeks and eyes with shorter detachment period. Disruptions of the IS and OS of photoreceptors and ELM on SDOCT examination after one month were observed in 37.04% of eyes, after 6 months in 29.6% of eyes, and at the end of the follow-up period in 14.8% of eyes. A statistically significant difference was found in the frequency of disruptions of the IS and OS, and ELM depending on the preoperative duration of RD (p = 0.007). Conclusion. The overall decrease in the mean retinal thickness after successful anatomical repair of RD is the result of a decrease in the thickness of the outer retinal layers. The alterations of the ELM, IS and OS of photoreceptors observed on the early SDOCT scans are mostly associated with limited vision recovery. The prolonged MD leads to damaging the neurosensory tissue of the retina and especially the photoreceptors, which may explain the limited visual acuity recovery after successful SB repair of RD
Keywords: eye diseases; macula lutea; retinal detachment; scleral buckling; tomography, optical coherence; treatment outcome; visual acuity